Modeling and analysis of hybrid multilevel converter for constant DC and fuel cell sources - Veerendra, A. S.; Mohd Rusllim, Mohamed; Mohd Herwan, Sulaiman; Leung, P. K. (John Wiley & Sons, Inc., 2020)
This article proposes a symmetrical hybrid multilevel converter topology with a constant DC source and a fuel cell source (FCS) for enhancing the voltage levels and minimization of total harmonic distortions (THD). The proposed topology is employed using a modified phase shifted pulse width modulation (PS‐PWM) in order to control the power electronic switches. In this hybrid topology, the first converter operated through low voltage with high frequency and the second converter through high voltage with fundamental frequency for improving the voltage levels. The THD for the hybrid multilevel converter with respect to current and voltage is 1.97% and 15.10%, respectively. The results show that the proposed topology performs better with a constant DC source compared to the fuel cell source. Furthermore, the less component count of the proposed topology is compared with the existing topologies. Comparisons are made to validate the results of the proposed topology with different sources and the existing topologies.